Mr. Taylor and the Central Bank : Two Inference Exercises - Luna, Francesco (IMF Working Papers; Working Paper ;, 2019)
Many observers argue that the world has changed after the latest financial crisis. If that is the case, monetary policy and the process informing it will have to be reconsidered and 'learned' anew by all stakeholders. Perhaps, a new Taylor rule will emerge. A 'Taylor rule' is predicated upon two successful inference exercises: one by the researcher who is interested in identifying the Central Bank's behavior and one by the Central Bank, which tries to infer how the economy works and interacts with its monetary policy interventions. Because of certain granularities imposed by institutional arrangements and the need for transparent communication in policy making, this paper proposes an analytical framework based on computability theory to model these inference exercises and to assess their general possibility of success. So, is it possible to infer/learn the central bank's policy rule? The answer is a qualified positive and depends on the 'complexity' of the economy and on the quality of information. As for policy implications, the results show that transparency and understandable 'reaction functions' will go a long way in fostering learnability.